EXPLORING STUDENTS’ CREATIVITY ON SOCIAL MEDIA IN LEARNING ENGLISH AT SMK KARTIKA XIX-3 CIREBON CITY: EXPLORING STUDENTS’ CREATIVITY ON SOCIAL MEDIA IN LEARNING ENGLISH AT SMK KARTIKA XIX-3 CIREBON CITY - Ika Maonik; Susilawati; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2023)
EXPLORING STUDENTS’ CREATIVITY ON SOCIAL MEDIA IN LEARNING ENGLISH AT SMK KARTIKA XIX-3 CIREBON CITY Ika Maoniks1*, Susilawati2, Eline Rozaliya Winarto3English Language Study Program, Teachers Training and Education Faculty, Universitas Muhammadiyah Cirebon, Cirebon, IndonesiaEmail: ikamaoniks3@gmail.com AbstractThe purpose of this study is to determine the rediness of exploring students creativity on social media in learning English. The subject and object of the study were 10 grade Nursing student at Kartika XIX-3 Vocational School Cirebon City, totaling 24 people including 22 girls and 2 boys. This study used qualitative methods. The study used questionnaires, interviews and observations as the instruments. The results of this students have positive perception about increasing creativity in social media for learning English content allowing them to store it practice their English skills especially listening,expandtheir vocabulary, and improve their pronounciation knowledge. Futhermore, as students can increase creativity in the use of social media for learning English in various forms They can select English content they enjoy on social media and learn about things their teacher doesn’t teach them in class. Due to this circumstance, students can feel at ease and inspired to practice their English outside of the classroom. Keywords: Students’ Creativity; Social Media; Learning Englis